PENERAPAN MODEL QUESTION STUDENT HAVE UNTUK MENINGKATKAN HASIL BELAJAR SEJARAH SISWA KELAS XI IPS3 SMA YPK PEMATANGSIANTAR - Abdul Azis Purba; Corry; Jalatua Habungaran Hasugian (Prodi Pendidikan Sejarah FKIP USI, 2026)
This research is motivated by the low learning outcomes of students in following Indonesian History lessons, this can be seen from the symptoms in the learning process. These symptoms indicate low student learning outcomes in the subject of Indonesian History, so that not a few students get scores below the KKM set by the school. The purpose of this study is to determine the Improvement of Student Learning Outcomes Through the Application of the Questions Students Have Method in the History Subject of class XI IPS3 at the Private High School Yayasan Perguruan Keluarga Pematangsiantar in the 2023/2024 Academic Year. This study uses Classroom Action Research (CAR). This research was conducted at the Private High School Yayasan Perguruan Keluarga Pematangsiantar in class XI IPS3 with a total of 32 students. The research stages include planning, implementation of actions, observation, and reflection. The results of the study showed a significant increase in student learning outcomes, from the category